Sustainable Supply Chain Management: Analyzing the past to determine a research agenda - Warley Henrique Silva; Patricia Guarnieri; José Márcio Carvalho; Josivania Silva Farias; Silvia Araújo dos Reis (Logistics, 2019)
The incorporation of sustainable aspects in the supply chain management (SCM) has become an important topic for researchers and professionals; however, it is a field that yet lacks a systemic understanding. The objective of this article is to conduct an analysis on the international literature about the SCM sustainability topic, by employing a systematic review protocol, covering the period from 2011 to 2016. The content analysis technique was performed, following the procedures of categorical thematic analysis proposed by Bardin (1977), which considers the creation of categories a posteriori, based in the direction senses related to the content analyzed. Besides to present the main characteristics of the articles related to distribution of publications per year, most studied sectors, main methods and approaches used main countries and journals of publications, we categorize the results at the systemic approach level of the sustainable development dimensions. We found that some dimensions are prominent when compared with the others: For example: the environmental one, on the other hand, the social one is approached few times in the papers considered in our analysis. These results also indicate that this type of discussion needs to be extended to other sectors that have not yet been explored. The contribution of this paper lies on the synthetization of the state-of-the-art related to sustainable SCM in the period considered, highlighting the environmental, social and economic dimensions, in order to identify a research agenda. By identifying possible research gaps, the results of this research contribute to guide future investigations on sustainable SCM, aiding researchers and practitioners in this field.
Keywords: 650; Green Supply Chain Management; Supply Chain Management; Sustainability; Sustainable Supply Chain Management